Long term outcomes of patients with chronic kidney disease after COVID-19 in an urban population in the Bronx - Jason Y. Lu; Justin Y. Lu; Stephen Wang; Katie S. Duong; Sonya Henry; Molly C. Fisher; Tim Q. Duong (Scientific Reports)
Abstract We investigated the long-term kidney and cardiovascular outcomes of patients with chronic kidney disease (CKD) after COVID-19. Our retrospective cohort consisted of 834 CKD patients with COVID-19 and 6,167 CKD patients without COVID-19 between 3/11/2020 to 7/1/2023. Multivariate competing risk regression models were used to estimate risk (as adjusted hazard ratios (aHR) with 95% confidence intervals (CI)) of CKD progression to a more advanced stage (Stage 4 or 5) and major adverse kidney events (MAKE), and risk of major adverse cardiovascular events (MACE) at 6-, 12-, and 24-month follow up. Hospitalized COVID-19 patients at 12 and 24 months (aHR 1.62 95% CI[1.24,2.13] and 1.76 [1.30, 2.40], respectively), but not non-hospitalized COVID-19 patients, were at higher risk of CKD progression compared to those without COVID-19. Both hospitalized and non-hospitalized COVID-19 patients were at higher risk of MAKE at 6-, 12- and 24-months compared to those without COVID-19. Hospitalized COVID-19 patients at 6-, 12- and 24-months (aHR 1.73 [1.21, 2.50], 1.77 [1.34, 2.33], and 1.31 [1.05, 1.64], respectively), but not non-hospitalized COVID-19 patients, were at higher risk of MACE compared to those without COVID-19. COVID-19 increases the risk of long-term CKD progression and cardiovascular events in patients with CKD. These findings highlight the need for close follow up care and therapies that slow CKD progression in this high-risk subgroup.